The Role of Environmental Legal Instruments and Government Policies in Realizing Sustainable Development in Indonesia - Muhammad Rahjay Pelengkahu; Najib Satria (Administrative and Environmental Law Review, 2023)
The increasing human needs have encouraged massive development in various countries, both developing and developed countries. in its progress, a development that is often carried out intersects with the environment. Also, various cases of pollution and environmental destruction due to development have been rampant. Therefore, a new paradigm in development is needed, which is contained in the concept of sustainable development. However, this requires the role of environmental law and government policies so that the goals of sustainable development can be realized. Sustainable development has the aim of balancing economic interests and environmental conservation so that the current development does not have a negative impact on future generations of humans. In general, the government has three types of policies in the environmental sector, namely, policies that are preemptive, preventive, and proactive. The writing of this law refers to a qualitative approach with a qualitative descriptive type of research. Through this research method, it is hoped that this legal writing will explain the role of law and government policy in realizing sustainable development in Indonesia. research results show The goal of sustainable development is to realize the development and utilization of natural resources to improve the quality of human life, without compromising the welfare of future human generations.